Automatically generation and evaluation of Stop words list for Chinese Patents - Deng Na; Chen Xu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
As an important preprocessing step of information retrieval and information processing, the accuracy of stop words’ elimination directly influences the ultimate result of retrieval and mining. In information retrieval, stop words’ elimination can compress the storage space of index, and in text mining, it can reduce the dimension of vector space enormously, save the storage space of vector space and speed up the calculation. However, Chinese patents are a kind of legal documents containing technical information, and the general Chinese stop words list is not applicable for them. This paper advances two methodologies for Chinese patents. One is based on word frequency and the other on statistics. Through experiments on real patents data, these two methodologies’ accuracy are compared under several corpuses with different scale, and also compared with general stop list. The experiment result indicates that both of these two methodologies can extract the stop words suitable for Chinese patents and the accuracy of Methodology based on statistics is a little higher than the one based on word frequency.